The Effect of Return on Equity, Current Ratio and Inventory Turnover on Earning Per Share in Large and Small Trade Sub-Sector Companies Listed on the IDX for the 2015-2019 Period - Shenjaya, Jesica; Haryanty, Cindy; Tan, Delfi; Valco, Enrique; Panggabean, Maya Sabirina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This Study aim for test and analyze influence Return On Equity, Current Ratio and Inventory Turnover To Earnings Per Share on Company subsector trade big and trading small which registered in Exchange Effect Indonesia period 2015-2019. The Method which used in study this use method study quantitative with type study descriptive quantitative which character explanatory research. Population study this is whole Company subsector trade big and trading small which registered in Exchange Effect Indonesia amount 61 company, Sample study this as much 10 company with technique taking sample purposive sampling. Method analysis data which used is regression linear multiple. Results study test f where f count 35,012 > f table 2.69 with level significant < 0.05 show by Return On equity, Current Ratio and Inventory Turnover by simultaneous take effect to Earnings Per Share. Results study test t where for variable Return On Equity have score t count 5,775 > t table 2.00247 or score Sig t (0.000) < (0.05) so that Return On Equity By Partial take effect positive and significant to Earnings Per Share. Variable Current Ratio have score t count 3,475 > t table 2.00247 or score Sig t (0.001) > (0.05) so that Current Ratio By Partial take effect positive and significant to Earnings Per Share and Inventory Turnover have score tcount 2,470 > ttable 2.00247 or score Sig t (0.017) < (0.05) so that Inventory Turnover By Partial take effect positive and significant to Earnings Per Share. Results analysis coefficient determination obtained score Adjusted R2as big as 0.637, it means variation variable Return On equity, Current Ratio and Inventory Turnover in explain variable Earnings Per Share is as big as 63.7%, whereas the rest as big as 36.3% explained by variable other.